2014
DOI: 10.1007/s00234-014-1426-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between glioma grades II and III in suspected low-grade gliomas using dynamic contrast-enhanced and dynamic susceptibility contrast perfusion MR imaging: a histogram analysis approach

Abstract: Histogram parameters from k(trans) (DCE) and rCBF (DSC) could most efficiently discriminate between grade II and grade III gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
3
47
1
Order By: Relevance
“…Previous studies in adult brain tumors have shown that higher-grade tumors have increased values of blood-brain barrier permeability measures like K trans , V e , and K ep [14,27,28] and these parameters were found to be useful for grading of gliomas. Vajapeyam et al [8] , in their recently published study, reported higher K trans and K ep values and lower V e values in higher-grade pediatric tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in adult brain tumors have shown that higher-grade tumors have increased values of blood-brain barrier permeability measures like K trans , V e , and K ep [14,27,28] and these parameters were found to be useful for grading of gliomas. Vajapeyam et al [8] , in their recently published study, reported higher K trans and K ep values and lower V e values in higher-grade pediatric tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological imaging included axial and coronal T2-weighted fluid attenuated inversion recovery (FLAIR) scans (0.45 × 0.45 × 6 mm 3 voxel size). Dynamic susceptibility contrast (DSC) perfusion imaging was performed as previously described [24], with a T2*W single-shot gradient echo-EPI sequence (1.7 × 2.3 × 5.0 mm 3 ). Whole-brain coverage was obtained using these parameters.…”
Section: Pet and Mri Acquisitionmentioning
confidence: 99%
“…DSC perfusion was analyzed as previously described [24], with calculation of CBV maps using nordicICE software (NordicNeuroLab AS, Bergen, Norway). Relative CBV (rCBV) was calculated as tumor-to-normal tissue (T/N) ratio by dividing the mean CBV in ROIs defined on PET, with the mean CBV within a reference area located in normal appearing white matter of the contralateral hemisphere above and lateral to the ventricle.…”
Section: Mri Perfusion Analysismentioning
confidence: 99%
“…It was reported that approximately 20 % of LGGs enhanced after the administration of a gadolinium-based contrast agent, whereas 14 %-45 % of nonenhancing gliomas were histologically proved to be HGGs [6,7]. It was reported that diffusion-weighted (DW) or PW imaging could differentiate HGGs from LGGs in nonenhancing gliomas [8,9], but no consensus has been reached in light of the limited number of studies.…”
Section: Introductionmentioning
confidence: 97%